Utilization of Some Weeds as Medicine by the Local People in Birbhum District of West Bengal, India - Chakraborty, Nihar Ranjan; Duary, Buddhadeb (International Journal of Bio-resource and Stress Management, 2014)
The present paper deals with observation on ethnomedicinal use of some weeds by the local people of Birbhum district, West Bengal. The traditional system of health care has been systematically used for over two thousand years to treat illnesses. The local people basically tribal people of this district many a time depend upon the forest flora for their livelihood and use some weeds as herbal medicines in curing the ailments and diseases. Most of the weeds have been known to posses therapeutic properties and the pertinent traditional knowledge was passed on orally through generations. Plants provide various medicines whose uses are without side effects. This knowledge has been threatened in its existence and is gradually being lost from society due to erosion of its culture. Finally total numbers of 20 plant species belonging to 18 families have been enumerated according to their botanical names along with families, local or tribal names, parts used, disease cured, mode of administration, etc. This folk knowledge of herbal medicine should be documented immediately before it gets lost forever and therapeutic validation of these herbal medicines is emphasized.